Survei Minat Bermain Sepakbola pada Siswi Putri Kelas V dan VI di SD Negeri Kendalserut I dan SD Negeri Kendalserut II Kabupaten Tegal - Cakra Yudha Wiratama; Andri Arif Kustiawan; Agus Pribadi; Bimo Alexander (MAN Insan Cendekia Jambi, 2026)
This study aims to determine the level of interest in playing football among female students in grades V and VI at SD Negeri Kendalserut I and SD Negeri Kendalserut II, Tegal Regency. The study employed a descriptive survey method with a mixed-methods embedded design approach, combining quantitative data from questionnaires with qualitative data from interviews and field observation. The research subjects consisted of 62 female students selected through purposive sampling based on cognitive and motor development criteria. The interest questionnaire (20 items, 5 indicators) was validated (r count > r table 0.361) and tested for reliability (Cronbach alpha = 0.87). Data validity was assessed using source triangulation. Results showed that the overall mean interest score was 55.2 (69.0%), categorized as High. SD Negeri Kendalserut I achieved 69.2% and SD Negeri Kendalserut II 68.6%, with a non-significant inter-school difference (0.6%). Supporting factors included peer support, an inclusive environment, and enjoyable learning. Main constraints were limited facilities and gender stigma. This study contributes to mapping female students' participation potential in football and identifies psychosocial factors as more dominant than material factors in shaping interest.